Time Series modeling and analysis of EEG Signal for wheelchair controller using Raspberry PI4 - Asst. Prof. Dr. Naufel Bahjat Mohammed (Genius Journals, 2023)
This paper discusses a Wheelchair controller based on an EEG signal collected from a person using Mindwave mobile 2 and processed by a Raspberry pi.4. A time series analysis was applied to build a statistical model to control a wheelchair with two DC motors.
Keywords: Modelling; EEG Signal; Wheelchair Controller